Socioeconomic inequalities in breast cancer mortality in microregions of the Brazilian Northeast - João Batista Carvalho; Neir Antunes Paes
Abstract Objectives: to evaluate the relation between the corrected mortality rates on breast cancer and the indicators of elderly women's living conditions in the Northeast micro-regions of Brazil . Methods: an ecological study was adopted in 2010 and 2015 for 188 micro-regions in the Northeast using structural equation modeling. The data on the population, deaths and indicators on living conditions were extracted from the IBGE, SIM/MS, and SISAP-Idoso (elderly), respectively. The under-registration of death data on breast cancer, badly defined death causes and garbage codes were corrected. The standardized mortality rates were calculated to permit time-space comparison. Results: the recovery of a considerable number of deaths was made possible to obtain a greater accuracy in the mortality rates estimation in micro-regions level. An increase in the mortality rates was observed at the time. The structural equation modeling presented a robust model with significance for some indicators on living conditions. The rates were higher in the micro-regions with lower percentage of illiterate elderly women, lower percentage of elderly women living in poverty, lower dependency ratio, and higher percentage of elderly women living at home with running water. Conclusions: the results showed an increased trend of elderly women dying of breast cancer in the region and with higher levels in the micro-regions with better indicators on living conditions.